THE IMPLEMENTATION OF TRI CORE BREASTFEEDING MODELS ON MOTHER’S SATISFACTION IN BREASTFEEDING - Siska Helina; Juraida Roito Harahap; Siti Halimah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
The low rates of exclusive breastfeeding have effected the growth and the development of children. Some efforts to improve the achievement of exclusive breastfeeding have been conducted, like an education about breastfeeding, facilitating early breastfeeding initiation and providing motivation to mothers. These elements contain a form of health promotion care model called the Tri Core Breastfeeding Models. The purpose of this study is to determine the effect of Tri Core Breastfeeding Models on breastfeeding mothers' satisfaction. This research was conducted in the working area of the Sidomulyo Health Center in Pekanbaru City in August 2019 to April 2020. This research is Pre-experimental Design. The population in this study was all third trimester pregnant women. The sample of 20 pregnant women was taken by consecutive sampling technique with 10 pregnant women in the intervention and 10 pregnant women for control. The Maternal Breastfeeding Evaluation Scale (MBFES) questionnaire was used to collect the data. The Mann Whitney Test with a significance level of 95% was used to analyze the data. The results showed that the average satisfaction of breastfeeding mothers in the intervention group was 134.80 (SD: 3.190) and the control group 119.10 (SD: 14.317), and it is found that there is a difference in breastfeeding satisfaction among mothers in the intervention group and the control group (p = 0.019). Finally, it is recommended that Tri Core Breastfeeding Models can be applied in providing midwifery care in the to support the success of exclusive breastfeeding